Curcumin enhances the anti‐cancer effects of Paris Saponin II in lung cancer cells. (2nd April 2018) - Man, Shuli; Zhang, Lili; Cui, Jingxia; Yang, Li; Ma, Long; Gao, Wenyuan
Abstract: Objectives: To investigate the synergistic mechanisms of Paris Saponin II (PSII) and Curcumin (CUR) in lung cancer. Materials and Methods: The combination changed the cellular uptake of CUR and PSII, apoptosis, cell cycle arrest and cytokine levels were analysed on different lung cancer cells. Results: The combination displayed a synergistic anti‐cancer effect through promoting the cellular uptake of CUR on different lung cancer cells. Hoechst H33258 staining and FACS assay indicated that the combination of PSII and CUR induced cell cycle arrest and apoptosis. Western blot and cytokine antibody microarray suggested that the combination activated death receptors such as DR6, CD40/CD40L, FasL and TNF‐α to induce cancer cells apoptosis, and up‐regulated IGFBP‐1 leading to inhibition of PI3K/Akt pathway and increase of p21 and p27, which therefore induced a G2 phase arrest in NCI‐H446 cells. Meanwhile, the combination suppressed PCNA and NF‐κB pathway in 4 kinds of lung cancer cells. They activated the phosphorylation of p38 and JNK, and inhibited PI3K in NCI‐H460 and NCI‐H446 cells, enhanced the phosphorylation of JNK in NCI‐H1299 cells, and increased the phosphorylation of p38 and ERK, and suppressed PI3K in NCI‐H520 cells. Conclusions: PSII combined with CUR had a synergistic anti‐cancer effect on lung cancer cells. These findings provided a rationale for using the combination of curcumin and PSII in the treatment of lung cancer in future.